Arthroscopic Evaluation Followed by Reconstruction of Both Anterior Cruciate Ligament (ACL) and Posterior Cruciate Ligament (PCL) Injuries (Journal of Rangpur Medical College, 2026)
Background: Knee ligament injuries involving combined anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) lead to substantial instability, often affecting young, active individuals following high-energy trauma. Objective: This study aimed to evaluate the outcomes of arthroscopic assessment followed by reconstruction of both the ACL and PCL in patients with combined knee ligament injuries. Methods: This prospective observational study was conducted at the Nilphamari Medical College, from July 2024 to June, 2025. All 80 patients aged 18-50 years had MRI-confirmed combined injuries and underwent standardized arthroscopic techniques using hamstring or alternative grafts. Functional improvement was assessed at 3, 6, and 12 months. Results: Most patients were men, primarily injured in road traffic accidents, and arthroscopy frequently revealed associated meniscal and cartilage lesions. By 12 months, Lysholm, IKDC, and Tegner scores improved significantly, with high overall satisfaction and a substantial return to sports. Complications remained modest, mainly arthrofibrosis and residual instability. Conclusion: Arthroscopic reconstruction yielded strong short-term recovery and functional restoration when combined with timely surgery and structured rehabilitation.J Rang Med Col.2026 Mar;11(1): 21-26